ASSESSMENT OF HEAVY METAL CONTAMINATION IN FISH AND WATER SAMPLES FROM BABBAN WUYA MADACHI RIVER: IMPLICATIONS FOR HUMAN HEALTH AND ENVIRONMENTAL SUSTAINABILITY - Yalwa, Lawan Musa; Durumin Iya, Sani Garba; Balarabe, Abubakar Ibrahim; Adamu, Suleiman Bashir (FUDMA Journal of Sciences, 2024)
This manuscript investigates the presence and concentration of heavy metals, namely zinc (Zn), copper (Cu), lead (Pb), and cadmium (Cd), in water and two commonly consumed fish species (Tilapia and Catfish) from the Babban Wuya Madachi River. Heavy metal contamination poses significant risks to both human health and environmental sustainability. The study employs Atomic Absorption Spectroscopy (AAS) to analyze heavy metal concentrations in water and fish samples collected from ten different points along the river. The mean concentration of Zn, Cu, Pb, and Cd in the Tilapia fish, Catfish and water are 50.85 ± 0.22, 2.84 ± 0.27, 7.89 ± 0.78, 0.80 ± 0.02 mg/kg; 33.87 ± 1.08, 1.49 ± 0.10, 3.74 ± 0.42, 0.33 ± 0.01mg/kg; and 0.07 ± 0.00, 0.09 ± 0.00, 0.05 ± 0.02, BDL mg/L respectively. Results indicate that water concentrations generally fall below World Health Organization (WHO) standards, while the concentrations of certain heavy metals in fish samples exceed WHO limits, notably Zn, Pb, and Cd. Moreover, concentration of Cu in fish samples is within the standard WHO limit of 2.25 mg/kg and in water its concentration is below the standard limit of 2mg/L. It has been reported that, heavy metals such as Zinc, Cd and Pb has a unique behavior that once absorbed by man it retained in the body system for long and accumulate to cause kidney problems and born demineralization through direct bone damage or indirect through renal dysfunction. The findings underscore the necessity of continued monitoring...
Keywords: Heavy metals; WHO; River; AAS; Fish; Water